2022
DOI: 10.3389/fvets.2022.999726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine hydroxy analog feed supplements: Significant alteration and enrichment of rumen microbiota and metabolome in Hu sheep

Abstract: Methionine hydroxy analogs (MHA) are widely used as the main sources of methionine in ruminant feed production. The purpose of this study was to explore the effect of using MHA supplements such as MHA as a salt of calcium (MHA-Ca) and 2-hydroxy-4-(methylthio)-butanoic acid isopropyl ester (HMBi) as sources of methionine on the rumen microbiota and metabolome in Hu sheep. Seventy-two healthy Hu sheep were randomly assigned to three dietary treatment groups: control, MHA-Ca, and HMBi groups. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The functional pathways involved in rumen microbes in this experiment were primarily related to metabolism, including carbohydrate metabolism, amino acid metabolism, and energy metabolism. This is in line with previous studies conducted on Tibetan sheep [ 66 ] and Hu sheep [ 67 ]. The addition of LBL did not have a significant impact on rumen microbiota-related functions and pathways compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…The functional pathways involved in rumen microbes in this experiment were primarily related to metabolism, including carbohydrate metabolism, amino acid metabolism, and energy metabolism. This is in line with previous studies conducted on Tibetan sheep [ 66 ] and Hu sheep [ 67 ]. The addition of LBL did not have a significant impact on rumen microbiota-related functions and pathways compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…There are several kinds of bacteria in the rumen, and various bacteria work together to degrade feed into metabolites, providing sufficient energy and nutrients for the host [44]. Thus, the rumen microbiota and rumen microbial fermentation are closely related to host productivity, health, and well-being [45]. Some studies have shown that different diets and feed additives can affect rumen fermentation and microbiota [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The rumen is a big microbial ecosystem consistuing of various rumen microbes, including bacteria, protozoa, fungi, and viruses [45]. The diversity and richness of rumen microbes are the key factors affecting rumen function [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…There are several kinds of bacteria in the rumen, and various bacteria work together to degrade feed into metabolites, providing sufficient energy and nutrients for the host [43]. Thus, the rumen microbiota and rumen microbial fermentation are closely related to host productivity, health, and well-being [44]. Some studies have shown that different diets and feed additives can affect rumen fermentation and microbiota [45,46].…”
Section: Discussionmentioning
confidence: 99%